2021
DOI: 10.1038/s41598-021-88511-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on effects of sweating treatment and different drying methods on the quality of Gentianae macrophyllae Radix

Abstract: To provide basis for improving the quality of Gentianae macrophyllae Radix and optimising the field processing method. Gentianae macrophyllae Radix samples were collected from Long County. Five main active iridoids were determined by using HPLC. The HPLC fingerprints were measured and analysed by the traditional Chinese medicine chromatographic fingerprint similarity evaluation system. Water, total ash, acid insoluble ash and ethanol extract contents were determined in accordance with Chinese Pharmacopoeia (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…As to G. macrophyllae Radix ( Qinjiao ), there are two kinds of processing methods in the Chinese Pharmacopoeia, namely, sweating and without sweating. According to Chen et al (2021), the contents of effective components (gentiopicroside and loganin acid) in the G. macrophyllae Radix samples dried after sweating treatment were significantly lower than those without sweating. In this study, the results showed that the DNA integrity was not affected significantly by sweating or not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As to G. macrophyllae Radix ( Qinjiao ), there are two kinds of processing methods in the Chinese Pharmacopoeia, namely, sweating and without sweating. According to Chen et al (2021), the contents of effective components (gentiopicroside and loganin acid) in the G. macrophyllae Radix samples dried after sweating treatment were significantly lower than those without sweating. In this study, the results showed that the DNA integrity was not affected significantly by sweating or not.…”
Section: Discussionmentioning
confidence: 99%
“…Sweating is a special treatment used for the drying of traditional Chinese medicinal herbs. Usually, herbs are slightly sun-dried, baked, or steamed and then stacked and wrapped to increase their temperature and make the internal water overflow (Chen et al, 2021). Each drying group was further divided into sliced and whole root groups, and the one with rhizomes removed was designated as a separate group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the samples were split into two parts. One part was used for UPLC-Q-TOF MS analysis and was quickly dried in an oven at 100 °C after being shredded [ 16 ]. The other part was collected in RNase-free tubes and quick-frozen in liquid nitrogen, before being stored at −80 °C in a refrigerator for later use.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the empirical theory of quality assessment from the character identification of TCM would be interpreted objectively based on the correlational analyses between appearance characteristics and active ingredients [ 3 ]. A growing number of researchers focus on the correlation between sensory features and chemical components, but research on single appearance signature are relatively common; for example, main active ingredients and quantitative color values were important bases for the quality evaluation of Gentianae macrophyllae radix with different drying methods [ 4 ]. The quality of Corni Fructus was closely related to its color, so it can be identified and graded by exterior color [ 5 ].…”
Section: Introductionmentioning
confidence: 99%